2017
DOI: 10.1027/1864-1105/a000181
|View full text |Cite
|
Sign up to set email alerts
|

Idealized Female Beauty, Social Comparisons, and Awareness Intervention Material

Abstract: Abstract. Previous research indicates that exposure to the idealized thin media standard of female beauty can contribute to body dissatisfaction, negative self-perception, depressed mood, and disordered eating. Importantly, studies have revealed that social comparison processes underlie this negative media effect: Women routinely compare themselves with the encountered mass-mediated thin ideals, which, in turn, elicits negative consequences. While there are a multitude of studies on this topic, little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Consistent with our second hypothesis (H2a), our findings indicated that, among girls, earlier pubertal timing was associated with increased media internalization over time. Given that early maturing girls experience greater body image discrepancy than on-time peers (McCabe, Ricciardelli, & Finemore, 2002), the direct pathway from pubertal timing to media internalization supports our suggestion that individuals with higher levels of body image concerns may compare their appearances with media models as a means to set personal standards for self-improvement (e.g., Arendt et al, 2017; Knobloch-Westerwick, 2015). This self-improvement hypothesis aligns with previous research, indicating that negative body evaluations are associated with more appearance-related comparisons among women (Blechert, Nickert, Caffier, & Tuschen-Caffier, 2009) and internalization of media-promoted appearance ideals among girls (Rodgers et al, 2015).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with our second hypothesis (H2a), our findings indicated that, among girls, earlier pubertal timing was associated with increased media internalization over time. Given that early maturing girls experience greater body image discrepancy than on-time peers (McCabe, Ricciardelli, & Finemore, 2002), the direct pathway from pubertal timing to media internalization supports our suggestion that individuals with higher levels of body image concerns may compare their appearances with media models as a means to set personal standards for self-improvement (e.g., Arendt et al, 2017; Knobloch-Westerwick, 2015). This self-improvement hypothesis aligns with previous research, indicating that negative body evaluations are associated with more appearance-related comparisons among women (Blechert, Nickert, Caffier, & Tuschen-Caffier, 2009) and internalization of media-promoted appearance ideals among girls (Rodgers et al, 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Negative affect, in turn, induces a motivation to reduce the actual-ideal discrepancy. One way to reduce self-discrepancy is through pushing the actual self in the direction of the ideal and/or ought self (Higgins, 1987) by setting self-improvement goals (e.g., Arendt, Peter, & Beck, 2017). In line with this, Knobloch-Westerwick (2015) indicated that individuals can reinforce their self-concept and minimize actual-ideal discrepancies such as appearance self-discrepancies through selectively attending to particular media content.…”
Section: Media As a Substitute Peer For Early Maturersmentioning
confidence: 99%
“…Two other studies investigating social comparison during the ED recovery process, found that the tendency to engage in virtual comparisons (i.e., via social media) with others who had been in ED treatment was related to increased ED psychopathology and ED-related clinical impairment (Saffran et al, 2016), and that individuals who attended a hospital-based treatment program engaged in more social comparison than age-matched controls without a clinical ED history (Bachner-Melman, Zontag-Oren, Zohar, & Sher, 2018). In non-clinical samples, social-comparison behaviors have been reduced through awareness campaigns administered in experimental settings (Arendt, Peter, & Beck, 2016). Despite being a malleable, proximal correlate of eating pathology, body-, eating-, and exercise-related social comparison is rarely measured in recovering samples, as researchers have yet to psychometrically evaluate and modify any existing measures of social comparison for use with this population.…”
Section: Social Comparison and Ed Recoverymentioning
confidence: 99%
“…In den Untersuchungen werden meist junge Studentinnen in Stichprobenauswahl nach Verfügbarkeit („convenience samples“) mit idealisierten Körperdarstellungen (etwa Bilder von Werbemodels, vgl. [ 10 , 11 ]) konfrontiert und danach zu ihrer Körperzufriedenheit und ähnlichen Konzepten, darunter oft auch die Neigung zu gestörtem Essverhalten, befragt. Als theoretische Grundlage fungieren dabei die „Theorie sozialer Vergleichsprozesse“ [ 12 , 13 ] sowie der „Kultivierungsansatz“ [ 14 – 16 ].…”
Section: Die Rolle Von Medien In Verschiedenen Phasen Einer Essstörununclassified